Stressed but still in the game - Andolšek, Jure (Kinesiologia Slovenica, 2025)
Elite athletes experience substantial psychological and physical stress that can undermine motivation and engagement in daily training and competition. Drawing on the Job Demands–Resources (JD-R) model, this study examines how daily sport-related stress affects sport engagement in elite athletes, focusing on the mediating role of attentional focus and the moderating role of REM sleep. Nineteen professional female handball players from Slovenia participated in a 60-day experience sampling study during the competitive season. Participants completed daily mobile surveys assessing stress, focus, and engagement, and wore validated Oura rings to track nightly REM sleep. In total, 1,020 daily observations were collected and analyzed using multilevel modeling. The results indicate that higher levels of perceived stress were associated with lower sport engagement the following day. This negative relationship was positively mediated by attentional focus: although stress tended to impair concentration, individuals who maintained higher attentional focus remained more engaged. Importantly, REM sleep moderated this relationship such that the negative impact of stress on engagement was slightly attenuated following nights with more REM sleep. The study extends JD-R theory by identifying REM sleep as a physiological buffer against stress. Practically, the results support interventions targeting stress management, attentional control, and sleep quantity to maintain sport engagement. We used a lagged daily design in which stress reported on Day 1 and REM sleep recorded during Night 1 predicted focus and engagement assessed on Day 2. The study demonstrates the value of combining self-reports with objective sleep tracking to understand within-athlete fluctuations in well-being and performance.
Keywords: motivation; motiviranje; sleep; spanje; sports; šport